The Protective Effect of Radish (Raphanus sativus) Seeds Against the Oxidative Stress Induced by Sodium Nitrite in Male Rabbits (Oryctolagus cuniculus) - Baghdad Science Journal (مجلة بغداد للعلوم)
The aim of this study is to investigate the protective effect of Radish (Raphanus sativus) seed alcoholic extract 70% against oxidative stress induced by sodium nitrite NaNO2 Twenty five adult male rabbits were devided into five groups of (five rabbits in each group) and treated daily for 30 days. Group T1: intubated orally 20 mg/kg NaNO2, Group T2: intubated orally 20 mg/kg NaNO2 + 50 mg/kg of alcoholic extract from Raphanus sativus seeds, Group T3: intubated orally 20 mg/kg NaNO2 + 100 mg/kg of alcoholic extract from Raphanus sativus seeds, Group T4: intubated orally 20 mg/kg NaNO2 + 200 mg/kg of alcoholic extract from Raphanus sativus seed as well as Group C: control intubated orally distilled water. In comparison with normal rabbits there were significantly increase in the level of Methemoglobin (MetHb%) , lipid peroxidation indicator malondialdehyde (MDA), and significantly decrease in the level of glutathione (GSH) in the rabbits intubated NaNO2. In rabbits intubated NaNO2 + 50,100,200 mg/kg of alcoholic extract it was found there were significant decreased in the level of MetHb%, MDA, and increase in the level of GSH. In conclusion according to results obtained from this study approved that alcoholic extract of Raphanus sativus seeds in dose (50,100,200 mg/kg) have protective effect against oxidative stress induced by sodium nitrite in male rabbits.